Corrigendum: Ethnopharmacological Approaches for Therapy of Jaundice: Part II. Highly Used Plant Species from Acanthaceae, Euphorbiaceae, Asteraceae, Combretaceae, and Fabaceae Families - Tewari, Devesh; Mocan, Andrei; Parvanov, Emil D; Sah, Archana N; Nabavi, Seyed M; Huminiecki, Lukasz; Ma, Zheng Feei; Lee, Yeong Yeh; Horbańczuk, Jarosław O; Atanasov, Atanas G (Frontiers in pharmacology, 2017)
[This corrects the article on p. 519 in vol. 8, PMID: 28848436.].
Keywords: phytoconstituents; alkaline phosphatase; oxidative stress; traditional use; bilirubin; jaundice; serum enzymes